The Perception of Pathumthani Residents Toward Its Environmental Quality, Suburban Area of Thailand - Iamtrakul, Pawinee; Chayphong, Sararad (Geographica Pannonica, 2021)
The urbanization process is often concentrated mostly in urban areas, resulting into urban development sprawl. This has effects on the lifestyles and activities of urban people, which in turn significantly affects the health of the city. The quality of the urban environment plays an important role in public health with respect to urban issues ranging from quality of utilities and services to quality of life. This study aims to study the perception of Pathumthani residents toward its environmental quality through spatial cluster analysis. A total of 1,000 sets of data collected from the interview survey among residents or commuters traveling through Pathumthani province was used for this study. The residents’ response towards environmental factors was examined through the classification of their different opinions among built environment and health aspects. The statistical analysis which was performed in this study was cluster analysis to demonstrate its relationship. With the level of satisfaction on environment aspect and health status in indicating number of congenital diseases, the result of this study found that condition of living environment (through Likert scale) affects the urban health with statistical significance of (P
Keywords: built environmental; health; satisfaction; quality of life; urbanization